Molecular diagnosis of two isolates of Pythium aphanidermatum causing the disease of seed rot and seedling damping-off in cucumber (Cucumis sativus L.) - Alwan, Sabah L.; AL-Abedy, Aqeel N.; Abdulzahera, Hussein I. (Journal of Kerbala for Agricultural Sciences, 2018)
This study was conducted to isolate and identify three isolates of the pathogenic fungus Pythium aphanidermatum causing seed rot and seedlings death in cucumber plants (Cucumis sativus L.) collected from three different regions, namely Abbasiya, Um-Abbasiyat and Qazwainiya in the province of Najaf. Pathogenicity test on cucumber seeds showed that all isolates from the three regions were pathogenic and caused seed rot. Isolate P. aphanidermatum from Al-Abbasiya region was the most aggressive isolate followed by the isolates obtained from Um-Abbasiyat and Qazwainiya regions that caused cucumber seed rot of 90, 74 and 72%, respectively; whereas no seed rot was seen in the control treatment. Results obtained from the polymerase chain reaction (P.C.R) of two most pathogenic isolates (P.a1 and P.a2) on cucumber seeds showed that it was possible to amplify 700-800 bp sized products. Results of the sequence analysis of nitrogen bases generated from the PCR-amplified products using BLAST showed that both isolates are belonging to the fungus P. aphanidermatum. The P.a2 was 100% identical to the globally isolated fungus that deposited at the National Center for Biotechnology Information (NCBI). The BLAST results showed that P.a1 had similarity of 98-998% with the isolates recoded at NCBI; therefore this isolate was registered in NCBI as a new isolate under the GenBank accession no. MF347709.